Impact of the SARS-CoV-2 pandemic on the screening of cervical cancer in the municipality of Taboão da Serra - SP (Research, Society and Development, 2022)
In Brazil, Primary Health Care is responsible for the early screening of neoplasms. Cervical Cancer is the second most prevalent cancer in the country. Its screening method is the oncotic colpocytology exam performed in women between 25 and 64 years of age who are sexually active. Objective: The present study aims to analyze the impact of the SARS-CoV-2 virus pandemic on cervical cancer screening in the municipality of Taboão da Serra - SP. Method: it was a cross-sectional observational study, with analysis of databases provided by the municipality of Taboão da Serra. Result: it was found that, in the respective municipality, the total number of Papanicolaou Test in women of eligible age (25 - 64 years), collected in 2019 was 6,276 and, in the following year, 2020, it was 4,207. There was an absolute reduction of 2,069 and a relative reduction of 32.97%. Conclusion: the study allowed us to analyze the impact of the SARS-CoV-2 pandemic on cervical cancer screening, however it was also observed that in the year before the pandemic, screening in the municipality was also deficient, so there is no guarantee that this screening is being effective in reducing morbidity and mortality.